Pengaruh Penambahan Maltodekstrin Pada Pembuatan Minuman Instan Serbuk Buah Pepaya (Carica papaya L.) dan Buah Pala (Myristica fragrans H.) - Michella C. Gabriela; Dekie Rawung; Maya M. Ludong (COCOS, 2020)
ABSTRACTA research on processing of instant drink powder was conducted utilizing under-valued and under-utilized nutmeg flesh and papaya fruit in spite of their high content of vitamins A and C, withaddition of maltodextrin. This product was expected to increase the profit of papaya’s andnutmeg’s farmers. Instant drink powder is a product that can be easily served by adding hot or coldwater and mix. Maltodextrine plays an essential role in processing of instant drink powder as filler.It also contributes to drying, flavoring and volume of the product. The results showed thatmaltodrxtrin has a protective effect to reduce heat destruction of vitamin C during instant drinkprocess. With 15% matodextrin addition resulted in product with the highest residual vitamin C(114.27 mg/100g). Sensory qualities were also improved with matodekstrin addition.